Anxiety Sensitivity and Panic Reactivity to Bodily Sensations: Relation to Quit-Day (Acute) Nicotine Withdrawal Symptom Severity Among Daily Smokers Making a Self-Guided Quit Attempt - Marshall, Erin C. (2009)
The current investigation explored the main and interactive effects of panic attacks in response to laboratory-induced bodily sensations and anxiety sensitivity in predicting acute nicotine withdrawal symptoms among daily smokers making a self-guided quit attempt. Participants were 99 daily smokers (58% women; M(age) = 28.4 years, SD = 11.7) who completed a battery of questionnaires, a voluntary hyperventilation challenge, and a measure of nicotine withdrawal symptoms 12 hr after making a self-guided quit attempt. Results indicated that the interaction of anxiety sensitivity and panic responsivity to the challenge predicted quit-day nicotine withdrawal symptom severity above and beyond the main effects (p < .05). The form of the interaction indicated that the relationship between postchallenge panic attack status and acute nicotine withdrawal was more robust among individuals who were low in anxiety sensitivity. Individuals who did not experience a panic attack posthyperventilation who were also low in anxiety sensitivity reported the lowest levels of nicotine withdrawal. Results suggest that anxiety sensitivity may be less relevant with regard to acute nicotine withdrawal severity among individuals with panic-related problems.